Vitamin D and the Human Antimicrobial Peptide LL-37 Enhance Group A Streptococcus Resistance to Killing by Human Cells - John F. Love (American Society for Microbiology, 2012)
ABSTRACT The CsrRS two-component regulatory system of group A Streptococcus (GAS; Streptococcus pyogenes) responds to subinhibitory concentrations of the human antimicrobial peptide LL-37. LL-37 signaling through CsrRS results in upregulation of genes that direct synthesis of virulence factors, including the hyaluronic acid capsule and streptolysin O (SLO). Here, we demonstrate that a consequence of this response is augmented GAS resistance to killing by human oropharyngeal keratinocytes, neutrophils, and macrophages. LL-37-induced upregulation of SLO and hyaluronic acid capsule significantly reduced internalization of GAS by keratinocytes and phagocytic killing by neutrophils and macrophages. Because vitamin D induces LL-37 production by macrophages, we tested its effect on macrophage killing of GAS. In contrast to the reported enhancement of macrophage function in relation to other pathogens, treatment of macrophages with 1α,25-dihydroxy-vitamin D3 paradoxically reduced the ability of macrophages to control GAS infection. These observations demonstrate that LL-37 signals through CsrRS to induce a virulence phenotype in GAS characterized by heightened resistance to ingestion and killing by both epithelial cells and phagocytes. By inducing LL-37 production in macrophages, vitamin D may contribute to this paradoxical exacerbation of GAS infection. IMPORTANCE It remains poorly understood why group A Streptococcus (GAS) causes asymptomatic colonization or localized throat inflammation in most individuals but rarely progresses to invasive infection. The human antimicrobial peptide LL-37, which is produced as part of the innate immune response to GAS infection, signals through the GAS CsrRS two-component regulatory system to upregulate expression of multiple virulence factors. This study reports that two CsrRS-regulated GAS virulence factors—streptolysin O and the hyaluronic acid capsule—are critical in LL-37-induced resistance of GAS to killing by human throat epithelial cells and by neutrophils and macrophages. Vitamin D, which increases LL-37 production in macrophages, has the paradoxical effect of increasing GAS resistance to macrophage-mediated killing. In this way, the human innate immune response may promote the transition from GAS colonization to invasive infection.